1952
DOI: 10.1085/jgp.36.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of the Photosensitized Inactivation of E. Coli and Reactivation Phenomenon

Abstract: Photosensitized inactivation of microorganisms has been the subject of numerous studies, and various hypothetical reaction mechanisms have been proposed for the interpretation of the phenomenon. In spite of such extensive experimentation and theorizing, there still exists uncertainty concerning the inactivation processes. No attempt will be made to review the subject since it has been analyzed and treated by Blum (1) and Arnow (2). It is evident that photosensitized inactivation is dependent on a variety of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1954
1954
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…It seems reasonable to assume that the small amount of inactivation under anaerobic conditions was due to a residue of oxygen which was not removed. These results are in agreement with those of Heinmets et al (1952) and Oster and McLaren (1950). It is e*ident that molecular oxygen is essential for the photodynamic inactivation of bacteriophage, as has been found for most other photodynamic systems studied.…”
Section: Resuij1ssupporting
confidence: 89%
See 1 more Smart Citation
“…It seems reasonable to assume that the small amount of inactivation under anaerobic conditions was due to a residue of oxygen which was not removed. These results are in agreement with those of Heinmets et al (1952) and Oster and McLaren (1950). It is e*ident that molecular oxygen is essential for the photodynamic inactivation of bacteriophage, as has been found for most other photodynamic systems studied.…”
Section: Resuij1ssupporting
confidence: 89%
“…The effect of changes in dye concentration may be seen from figure 2. At low concentrations the inactivation rate is directly proportional to dye concentration, presumably because only adsorbed dye is effective in photodynamic inactivation (Heinmets et al, 1952) and the amount of dye adsorbed is proportional to its concentration. At higher concentrations the inactivation rate reaches a maximum and then decreases because the filtering effect of the dye decreases the effective light intensity.…”
Section: Resuij1smentioning
confidence: 99%
“…Subsequently different authors have described reduction of several pathogens to different extent. This includes Herpes simplex [28], Escherichia coli [29], and vaccinia virus [30]. Today it is well established that combined MB light system has a broad spectrum potential for reducing the impact of pathogens transmittable through transfusion.…”
Section: Biochemical Characteristics Of Methylene Bluementioning
confidence: 99%
“…Furthermore, at -700C, no activity was observed for any of the enzymes named during a 27-day period, while the photochemical transformation of protochlorophyll proceeded quite rapidly at this temperature. Because of these facts, it is concluded that the reaction is controlled by photochemical activation rather than by enzyme activation (2,3).…”
Section: Resultsmentioning
confidence: 99%